Clec9a-Mediated Ablation of Conventional Dendritic Cells Suggests a Lymphoid Path to Generating Dendritic Cells In Vivo - Salvermoser, Johanna; van Blijswijk, Janneke; Papaioannou, Nikos E.; Rambichler, Stephan; Pasztoi, Maria; Pakalniškytė, Dalia; Rogers, Neil C.; Keppler, Selina J.; Straub, Tobias; Reis e Sousa, Caetano; Schraml, Barbara U. (Frontiers in Immunology, 2018)
Abstract: Conventional dendritic cells (cDCs) are versatile activators of immune responses that develop as part of the myeloid lineage downstream of hematopoietic stem cells. We have recently shown that in mice precursors of cDCs, but not of other leukocytes, are marked by expression of DNGR-1/CLEC9A. To genetically deplete DNGR-1-expressing cDC precursors and their progeny we crossed Clec9a-Cre mice to Rosa-lox-STOP-lox-Diphtheria toxin (DTA) mice. These mice develop signs of age dependent myeloproliferative disease, as has been observed in other DC deficient mouse models. However, despite efficient depletion of cDC progenitors in these mice, cells with phenotypic characteristics of cDCs populate the spleen. These cells are functionally and transcriptionally similar to cDCs but show somatic rearrangements of Ig-heavy chain genes, characteristic of lymphoid origin cells. Our studies reveal a previously unappreciated developmental heterogeneity of splenic cDCs and suggest that the lymphoid lineage can generate cells with features of cDCs when myeloid cDC progenitors are impaired.